THE INFLUENCE OF MARKETING MIX ON CUSTOMER LOYALTY AT KOPI JANJI JIWA SUKARAME: ELECTRONIC WORD OF MOUTH AS AN INTERVENING VARIABLE - Meysi Susila Gayatri; Andhyka Tyaz Nugraha; Rizqi Wahyudi (Jurnal Ilmiah Teknik Industri, 2025)
This study aims to analyze the influence of the marketing mix on customer loyalty, along with the role of Electronic Word of Mouth (E-WOM) as an intervening variable. Google Form was used as the data collection instrument, targeting 126 customers of Kopi Janji Jiwa Sukarame selected as respondents. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied in this research and processed using SmartPLS 3.0 software. The findings reveal that all dimensions of the marketing mix have a positive effect on both E-WOM and customer loyalty. E-WOM was also found to influence customer loyalty positively and to intervene in the relationship between the marketing mix and customer loyalty. These findings highlight the importance of effective marketing strategy management in building long-term customer loyalty while encouraging the spread of positive information among consumers, which ultimately contributes to the sustainability of customer loyalty.